Metastatic tumor cells detection and anti‐metastatic potential with vesicular stomatitis virus in immunocompetent murine model of osteosarcoma. Issue 9 (8th May 2018) - Johan, Muhammad P.; Kubo, Tadahiko; Furuta, Taisuke; Sakuda, Tomohiko; Sakaguchi, Takemasa; Nakanishi, Mahito; Ochi, Mitsuo; Adachi, Nobuo
ABSTRACT: Sarcomas are associated with a high incidence of lung metastasis, which leads to a high‐risk of cancer death. This study was performed to explore the pre‐clinical theranostic potential of a novel fully functional recombinant vesicular stomatitis virus carrying imaging gene Katushka (rVSV‐K), as virotherapy and circulating tumor cells (CTCs) detection in the syngeneic mouse model of osteosarcoma with spontaneous pulmonary metastases. Recombinant VSV‐K was generated and evaluated in vitro on human and murine osteosarcoma cells. Spontaneous osteosarcoma metastases were established in immune‐competent mice by implanting subcutaneously syngeneic osteosarcoma LM8 cells. The vector was injected into the tumor‐bearing mice via jugular vein either once or repeatedly. To assess effectiveness, primary tumor growth and development of lung metastasis as well as survival were evaluated. We found that rVSV‐K efficiently replicated in and killed all osteosarcoma cell lines in time‐dependent manners. Both single or repeated systemic injections of the virus did not inhibit the growth of the primary tumor, but the repeated administration could effectively suppress the development of lung metastases and was likely responsible for the observed increase in survival. Furthermore, we demonstrated, for the first time, that CTCs in blood samples from syngeneic osteosarcoma‐bearing mice were successfully detected by utilizing rVSV‐K ex vivo. Our results show that repeated systemic injections of rVSV‐K are an effective anti‐metastatic agent against osteosarcoma in immune‐competent mice and this virus to be a useful tool for detection of osteosarcoma CTCs, suggesting that further development of future viral‐based theranostic approach in patients with osteosarcoma is warranted. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:2562–2569, 2018. Abstract : Osteosarcoma presenting metastatic disease remains a major problem with limited treatment options. Our findings show that repeated systemic injections of recombinant vesicular stomatitis virus carrying imaging genes, Katushka (rVSV‐K) could effectively suppress the development of lung metastasis in osteosarcoma‐bearing mouse model. Furthermore, circulating tumor cells in blood samples were successfully detected by utilizing rVSV‐K ex vivo transfection. These results indicate that this virus may represent a particularly attractive vector platform for viral‐based theranostic agents (therapeutic and diagnostic) against osteosarcoma.